2008
DOI: 10.1016/j.appet.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Body dissatisfaction mediates the association between body mass index and risky weight control behaviors among White and Native American adolescent girls

Abstract: The developmental path leading to eating disorders among adolescent girls often proceeds from increasing body size, to increasing body dissatisfaction, to increasing ED risk. To determine whether body dissatisfaction (BD) mediates the association between body size and risky weight control behaviors, we examined data from White (n = 709) and Native American (n = 253) girls, who differ substantially in terms of average body mass and reported weight control behaviors. Measures of BD included weight, shape, and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
1
17
0
2
Order By: Relevance
“…Moreover, as expected, parents with a higher BMI would have a higher level of body dissatisfaction as stated in Table 8, which was consistent with previous researches showing the positive association between BMI and body dissatisfaction [7,13,15]. Similar phenomena were also observed in PDR.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, as expected, parents with a higher BMI would have a higher level of body dissatisfaction as stated in Table 8, which was consistent with previous researches showing the positive association between BMI and body dissatisfaction [7,13,15]. Similar phenomena were also observed in PDR.…”
Section: Discussionsupporting
confidence: 80%
“…The association of body mass index and body dissatisfaction had been consistently demonstrated in researches [12][13][14], in which recent studies had also shown that the increase in BMI can significantly predict the increase in body dissatisfaction in the same period of time [7,13,15].…”
Section: Pathway: Bmi -Body Dissatisfactionmentioning
confidence: 99%
“…Van Den Berg et al (2007) showed that males and females are dissatisfied with their bodies, but quite differently affected by the variables which mediate body dissatisfaction. Similarly, Lynch et al (2008) found that body dissatisfaction is present in both males and females, and it is a highly significant mediator of the relationship between BMI, body size, risky weight control behaviors, and vulnerability to eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Body image perception was assessed in both eating disordered (Matos et al, 2002;Vander Wal & Thomas, 2004;Legenbauer, Rühl & Vocks, 2008) and body dysmorphic disordered populations. Nowadays, research on body image has mostly focused on body image dissatisfaction among the normal population (Fingeret, Gleaves & Pearson, 2004;McCabe, Ricciardelli, Sitaram & Mikhail, 2006;Van Den Berg et al, 2007;Neighbors & Sobal, 2007) in order to identify discrepancies in body image perception (Cachelin, Monreal & Juarez, 2006;Steenhuis, Bos & Mayer, 2006), which have been considered for the prevention and the treatment of a variety of other disorders (Matos et al, 2002), especially the ones involving behavioral changes (Lynch, Heil, Wagner & Havens, 2008) and/or the promotion of well-being and quality of life (Damasceno, Lima, Vianna, Vianna & Novaes, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Lynch et al, (2007) found that regardless of ethnicity or gender, BMI was positively correlated with body concerns and weight control behaviors. Lynch et al, (2008) found that body dissatisfaction was a highly significant mediator of the relationship between body mass index (BMI) and eating disorder risk although, body dissatisfaction did not mediate the association between BMI and binge eating but it is apparently an important mediator of the association between body size and some risky weight control behaviors. Lofrano-Prado et al, (2011) revealed that BMI and fat mass increase the risk of developing eating disorder and body image dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%